THE POLITICS OF POLICYMAKING : an Introduction - Boin, Arjen; Lodge, Martin (Sage, 2024)
"Open up the black box of government to see where policies are made. As soon as a politician sets a new policy target, policymakers set to work to make things happen. This introductory text takes you beyond he world of classic theories and models and into the messy world of policymaking, offering a toolkit for enhancing policy outcomes. Drawing from insights earned through years of interactions with policymakers and extensive teaching experience, Boin and Lodge offer a comprehensive introduction to the inner workings of government and how to produce policies that address societal problems of today and tomorrow."-- Back cover